The Analysis of Class Management Ability to Improve Students’ Activity on Mathematics Learning Process at Grade 8 SMP Swasta Pab 2 Helvetia - Losi, Nanda Tia; Siregar, MY; Puspaningrum, Cici (Journal of Mathematics and Mathematics Education, 2020)
In the teaching and learning process, teacher is not only required to have knowledge to be given to his students. But teachers are required to have the ability to manage the class well. This research aimed to explain students’ activity and the class management to overcome students’ learning difficulty on Mathematics learning. This research used qualitative approach. The subject of research was the mathematic teachers and grade 8 students at SMP PAB 2 Helvetia. The data was collected by observation, interview, and documentation. The research result showed that mostly teachers managed the class well, physically and non-physically. It was seen by the following percentage: (1) physic management for 50% and  non-physic management for 52.94% (Teacher of G-1), (2) physic management for 33.33% and non-physic management for 35.30% (Teacher of G-2).As for students’ activity at grade 8-1by the following percentage: (1) Visual activities 66.22%; (2) Oral activities 52.70%; (3) Listening activities 73.65%; (4) Writing activities 73.65%; (5) Drawing activities 0%; (6) Motor activities 0%; (7) Mental activities 52.70%; (8) Emotional activities 54.05%. Students’ activity at grade 8-5 by the following percentage: (1) Visual activities 42.50%; (2) Oral activities 30.63%; (3) Listening activities 41.25%; (4) Writing activities 46.88%; (5) Drawing activities 0%; (6) Motor activities 0%; (7) Mental activities 33.75%; (8) Emotional activities 28.75%.